PEMANFAATAN PUPUK ORGANIK CAIR UNTUK MENINGKATKAN SERAPAN NITROGEN SERTA PERTUMBUHAN DAN PRODUKSI SAWI (Brassica juncea L.) PADA TANAH BERPASIR - Monica Febrianna; Sugeng Prijono; Novalia Kusumarini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
Mustard is a kind of vegetable that is favored by the public. Liquid organic fertilizer (LOF) mixture of leaves of gamal, chicken manure, and coconut water has a high nitrogen content, so they can increase the nitrogen needed by mustard planted on sandy soil. The purposes of this study were (i) to test the influence of nitrogen absorption LOF deployment against mustard plants, and (ii) to analyse the application influence of LOF deployment against the chemical properties of soil and growth and yield of mustard plant. This study used a randomized completely design with twelve treatments and three replicates. The treatments were as follows: without LOF or watering with tap water as a control (A0), LOF with watering every 2 days (I1), LOF withwatering every 4 days (I2), and LOF with watering every 6 days (I3), LOF 0% dose concentration (P0), LOF 50% dose concentration (P1), LOF 100% dose concentration (P2), and LOF 150% dose concentration (P3). The result showed that application of liquid organic fertilizer significantly affected pH, organic-C, total-N, Uptake of N, and towards growth and yield of mustard plant. The the best yield was in the I2P2 treatment